2013
DOI: 10.1016/j.cell.2013.01.053
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/CXCL12 Mediate Autocrine Cell- Cycle Progression in NF1-Associated Malignant Peripheral Nerve Sheath Tumors

Abstract: Malignant Peripheral Nerve Sheath Tumors (MPNSTs) are soft tissue sarcomas that arise in connective tissue surrounding peripheral nerves. They occur sporadically in a subset of patients with Neurofibromatosis type-1 (NF1). MPNSTs are highly aggressive, therapeutically resistant, and typically fatal. Using comparative transcriptome analysis, we identified CXCR4, a G protein-coupled receptor, as highly expressed in mouse models of NF1-deficient MPNSTs, but not in non-transformed precursor cells. The chemokine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 55 publications
9
125
1
1
Order By: Relevance
“…As part of this effort, several laboratories have explored the possibility that aberrant growth factor signaling is a key upstream mediator of Ras activation in MPNSTs. These studies identified several growth factors and growth factor receptors that potentially contribute to neurofibroma and MPNST pathogenesis, including the epidermal growth factor (EGF) receptor, 24 neuregulin-1 (NRG1), 24 platelet-derived growth factor, 24 hepatocyte growth factor, and its c-Met receptor, 24 the insulin-like growth factor 1 receptor, 51 transforming growth factor-b1, 52 lysophosphatidic acid, 53 midkine, 52 Kit ligand and its c-Kit receptor, 24 CXCR4 and its CXCL12 ligand, 54 basic fibroblast growth factor, and vascular endothelial growth factor. 55 However, the strength of the evidence…”
Section: Genomic Abnormalities Mediating Neurofibroma-mpnst Progressionmentioning
confidence: 99%
“…As part of this effort, several laboratories have explored the possibility that aberrant growth factor signaling is a key upstream mediator of Ras activation in MPNSTs. These studies identified several growth factors and growth factor receptors that potentially contribute to neurofibroma and MPNST pathogenesis, including the epidermal growth factor (EGF) receptor, 24 neuregulin-1 (NRG1), 24 platelet-derived growth factor, 24 hepatocyte growth factor, and its c-Met receptor, 24 the insulin-like growth factor 1 receptor, 51 transforming growth factor-b1, 52 lysophosphatidic acid, 53 midkine, 52 Kit ligand and its c-Kit receptor, 24 CXCR4 and its CXCL12 ligand, 54 basic fibroblast growth factor, and vascular endothelial growth factor. 55 However, the strength of the evidence…”
Section: Genomic Abnormalities Mediating Neurofibroma-mpnst Progressionmentioning
confidence: 99%
“…Therefore, a CXCR4 antagonist with desirable in vivo pharmacologic and toxicologic properties would have potential for treatment of human cancers. Interruption of CXCR4 and SDF-1 axis has demonstrated antitumor growth activities in a variety of preclinical tumor models (2,3,(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor-secreted growth factors can affect tumor microenvironment (1,2), as well as stimulate the cancer cells themselves to proliferate and develop a more malignant phenotype in an autocrine manner (3)(4)(5)(6). A variety of growth factors and cytokines exert their effects on cancer cells by activating the membrane-associated phosphoinositide 3-kinase (PI3K)/AKT signaling pathway, which regulates a wide spectrum of cellular functions, including proliferation, survival, angiogenesis, invasion, and metastasis.…”
Section: Introductionmentioning
confidence: 99%